2021
DOI: 10.1016/j.ynstr.2021.100346
|View full text |Cite
|
Sign up to set email alerts
|

Variations in response to trauma and hippocampal subfield changes

Abstract: Models of posttraumatic stress disorder (PTSD) suggest that the hippocampus is key to the persistence of traumatic memory. Yet very little is known about the precise changes that take place in this structure, nor their relation with PTSD symptoms. Previous studies have mostly used magnetic resonance imaging (MRI) at low resolutions, making it impossible to identify sensitive anatomical landmarks, or compared groups often unequally matched in terms of traumatic exposure. The present cross-sectional study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 84 publications
(135 reference statements)
0
41
0
Order By: Relevance
“…An overview of the literature review for psychosocial factors and their associations with hippocampal subfield volumes are displayed in Table 1 . Of the 47 articles, 27 studies (57%) reported lower hippocampal subfield volumes in the presence of a psychosocial factor, specifically depression (Averill et al, 2017 ; Choi et al, 2017 ; Doolin et al, 2018 ; Frodl, Carballedo, et al, 2014 ; Frodl, Skokauskas, et al, 2014 ; Han et al, 2016 ; Han et al, 2019 ; Huang et al, 2013 ; Mikolas et al, 2019 ; Postel et al, 2021 ; Su et al, 2016 ; Travis et al, 2015 ; Treadway et al, 2015 ; Wisse et al, 2015 ; Zhou et al, 2020 ), anxiety (Takaishi et al, 2021 ), or childhood maltreatment or post‐traumatic stress disorder (PTSD) (Aghamohammadi‐Sereshki et al, 2021 ; Ahmed‐Leitao et al, 2019 ; Averill et al, 2017 ; Chalavi et al, 2015 ; Chen et al, 2018 ; Hayes et al, 2017 ; Janiri et al, 2019 ; Lim et al, 2012 ; Luo et al, 2017 ; Postel et al, 2021 ; Wang et al, 2010 ; Yuan et al, 2020 ; Zhang et al, 2021 ). The most often affected subfields were the CA3 and DG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of the literature review for psychosocial factors and their associations with hippocampal subfield volumes are displayed in Table 1 . Of the 47 articles, 27 studies (57%) reported lower hippocampal subfield volumes in the presence of a psychosocial factor, specifically depression (Averill et al, 2017 ; Choi et al, 2017 ; Doolin et al, 2018 ; Frodl, Carballedo, et al, 2014 ; Frodl, Skokauskas, et al, 2014 ; Han et al, 2016 ; Han et al, 2019 ; Huang et al, 2013 ; Mikolas et al, 2019 ; Postel et al, 2021 ; Su et al, 2016 ; Travis et al, 2015 ; Treadway et al, 2015 ; Wisse et al, 2015 ; Zhou et al, 2020 ), anxiety (Takaishi et al, 2021 ), or childhood maltreatment or post‐traumatic stress disorder (PTSD) (Aghamohammadi‐Sereshki et al, 2021 ; Ahmed‐Leitao et al, 2019 ; Averill et al, 2017 ; Chalavi et al, 2015 ; Chen et al, 2018 ; Hayes et al, 2017 ; Janiri et al, 2019 ; Lim et al, 2012 ; Luo et al, 2017 ; Postel et al, 2021 ; Wang et al, 2010 ; Yuan et al, 2020 ; Zhang et al, 2021 ). The most often affected subfields were the CA3 and DG.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies used 1.5T or 3T MRI, with four studies (9%) using high‐field 7T MRI (Brown et al, 2019 ; Kraus et al, 2019 ; Tannous et al, 2020 ; Wisse et al, 2015 ). Twenty‐four studies (51%) reported no significant differences in volume (Abbott et al, 2014 ; Brown et al, 2019 ; Burhanoglu et al, 2021 ; Cao et al, 2017 ; Chalavi et al, 2015 ; Frodl, Carballedo, et al, 2014 ; Han et al, 2016 ; Hansen et al, 2021 ; Hu et al, 2019 ; Kakeda et al, 2018 ; Lim et al, 2012 ; Lindqvist et al, 2014 ; Liu et al, 2021 ; Na et al, 2014 ; Na et al, 2018 ; Ota et al, 2017 ; Postel et al, 2021 ; Szymkowicz et al, 2017 ; Tannous et al, 2020 ; Taylor et al, 2020 ; Travis et al, 2015 ; Travis et al, 2016 ; Weis et al, 2021 ; Yuan et al, 2020 ), and four studies (9%) found increased volumes, specifically in the left hippocampal amygdala transition area (HATA) for sexual abuse (Ahmed‐Leitao et al, 2019 ), the hippocampal tail in those with major depressive disorder (MDD) (Maller et al, 2018 ), the CA1, CA3, and molecular layer in those with childhood maltreatment (Mikolas et al, 2019 ), and in the right subiculum in those with MDD (Kraus et al, 2019 ). No studies assessed recent stressful life events or social support.…”
Section: Resultsmentioning
confidence: 99%
“…Traumatic stressors have also been shown to alter hippocampal dendritic morphology and inhibit neurogenesis in the hippocampus [ 42 , 44 , 45 , 46 ]. Chronic stress rapidly reduces the number of dendritic spines and branches of pyramidal neurons in the Cornu Ammonis subfield 3 (CA3) and compromises the integrity of CA1, which is involved in the persistence and re-experiencing of traumatic memories [ 47 , 48 ]. For example, early magnetic resonance imaging studies demonstrated smaller hippocampal volumes in Vietnam Veterans with PTSD compared with controls [ 49 , 50 , 51 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sections were mounted, dried, and stained with cresyl violet. Here we report data obtained for the dentate gyrus of the dorsal hippocampus; an area related to emotional reactions ( Ballesteros et al, 2014 ; Postel et al, 2021 ). Images of the area of interest were taken with an optic microscope (MEIJI MT4200H) and a digital camera Canon (EOS—850D) of 20Mp.…”
Section: Methodsmentioning
confidence: 99%